Colopleurocutaneous fistula associated with empyema as a late complication of colorectal cancer - Milan Savic; Zeljko Garabinovic; Nikola Colic; Marko Kostic; Miljan Ceranic; Jovan Peric; Mihailo Stjepanovic (Journal of Infection in Developing Countries)
Introduction: Pleurocutaneous fistula is a pathological communication of subcutaneous tissue with the pleural cavity, and can occur as a result of infectious, malignant processes and iatrogenic procedures. Colopleural fistula is rare and is mainly caused by processes in the abdomen. The appearance of empyema is usually described as a complication of colopleural fistulas that are the result of pathological processes in the abdomen.